Analysis of the relative risk factors for H-type hypertension and its correlation with the MTHFR C677T genotype in a health checkup population in Urumqi, China—a cross-sectional study - Na Li; Xiaoping Yang; Yuan Zou; Jing Chen; Yajing Cui; Yunjie Teng; Dan Yang; Ayipali Aikemujiang; Jianrong Wu (BMC Cardiovascular Disorders)
Abstract Background This cross-sectional survey investigated the incidence of H-type hypertension and associated risk factors in a health checkup population in Urumqi, China. We aimed to identify potential intervention targets by screening patients with H-type hypertension and high-risk populations, filling the gap in the risk assessment of H-type hypertension in high-altitude areas. Methods From January 2023 to January 2024, we conducted a cross-sectional study on 1,772 individuals who underwent methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism evaluations. We included a questionnaire survey and collected physical measurements and blood samples. The relative risk factors related to H-type hypertension, as well as their correlation with the MTHFR C677T genotype, were subsequently analyzed. Results H-type hypertension was present in 68.96% of hypertension cases and 17.55% of the population in Urumqi who underwent health checkups. The methylenetetrahydrofolate reductase (MTHFR) C677T distributions of the CC, CT, and TT genotypes were 11.90%, 39.87%, and 48.23%, respectively. Moreover, multivariate logistic regression identified the MTHFR C677T TT genotype, age, triglyceride-glucose index (TyG), and carotid plaques as risk factors related to H-type hypertension, with odds ratios (ORs) of 3.044 (p < 0.001), 1.041 (p = 0.001), 1.385 (p = 0.003), and 1.748 (p < 0.001), respectively. In addition, high-density lipoprotein (HDL) cholesterol was identified as a protective factor (OR = 0.447, p = 0.002). Through regression analysis, a nomogram model was constructed to predict the incidence of H-type hypertension. This model showed a good fit, and the area under the receiver operating characteristic (ROC) curve (AUC) was 0.760. Its predicted H-type hypertension incidence was closely related to the actual incidence. Conclusions According to our findings, the MTHFR C677T TT genotype in Urumqi, China, serves as a risk locus related to H-type hypertension. Moreover, age, TyG, and carotid plaques are risk factors for H-type hypertension, whereas HDL is a protective factor.